ASAS-ASAS KONTRAK (AKAD) DALAM HUKUM SYARI’AH - Akhmad Hulaify (Islamic University of Kalimantan MAB Banjarmasin, 2019)
The position of the principles of contract (aqad) in Sharia law is a form protection of rights for economic transactions. This study examines the principles of contract (aqad) in sharia. This type of research is a library research. While the approach used in this study; normative approaches, sociological approaches, historical approaches and philosophical approaches. Data obtained from the literature were carried out reduction and classified then carried out to find the relationship between the data found with the core problem of this study. These results are analyzed using the method of analysis content with the aim of finding answers to the problems of this study. After analysis can be found the red thread that in Islamic Economics, contract is a determining factor of the immaturity of economic transactions. The emphasis is on the principle of circulation, principle of guarding, and principle of justice. The purpose of this study is to provide knowledge and understanding to the community that the principles of contract (aqad) in sharia are not only a form of agreement on a transaction but also as a bond between the two parties specifically regulated in the Islamic Economic system in order to avoid the mudharat (damage) and the safety of the world and hereafter (falah).